New records of Calappa tuerkayana Pastore, 1995 (Brachyura, Calappidae) from the central Mediterranean - Pipitone, Carlo (Array, 2018)
Two specimens of the uncommon calappid crab Calappa tuerkayana Pastore, 1995 are reported from the central Mediterranean. One juvenile individual was caught in a trawl net at about 105 m depth on a detritus bottom, and one adult male was caught in a trammel net at 50 m depth in a similar habitat. Details about carapace ornamentation and fresh color of the adult, which complement previous descriptions are provided. Family Calappidae includes four species in the Mediterranean Sea. C. tuerkayana has been recorded a few times from its known geographic range. These are the southernmost records to date.